Pengukuran Risiko Indeks Keamanan Informasi(Kami) Bagian Tata Kelola Kota XYZ Menggunakan Framework Nist Sp 800-30 - Juliharta, I Gede Putu Krisna; Adrian, A; Erawan, Ayu Pradnyandari Dananjaya (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2024)
The XYZ City Government has conducted an assessment using the KAMI Index, revealing that the governance aspect is weaker compared to other areas. Given this issue, a risk assessment was conducted to provide recommendations for the City of XYZ to improve its information security. The risk assessment was carried out using the NIST SP 800-30 framework, designed as a guideline for evaluating risk management. There are five risk categories: Very Low, Low, Moderate, High, and Very High. Based on the assessment using NIST 800-30, several critical areas for improvement were identified: Policy with a High level of risk, Data and Information with a Very High level of risk, Information Security Education with a Moderate level of risk, Accountability with a High level of risk, Implemented Programs with a High level of risk, Legal Aspects with a High level of risk, BCP and DRP Implementation with a High level of risk, Information Security Standards and Performance with a Moderate level of risk, and Information Security Management with a High level of risk.